Impact of direct and indirect taxes on economic development: A comparison between developed and developing countries - Taufik Abd Hakim; Abdul Aziz Karia; Jasmine David; Rainah Ginsad; Norziana Lokman; Salwa Zolkafli (Cogent Economics & Finance, 2022)
Taxes have extraordinary roles in any country's economic development and policymaking. This study extends prior studies by investigating the impact of direct and indirect taxes on the economic development of 47 developed and 90 developing countries. All data about the variables involved in the study are accessed from the World Bank, covering from 2000 to 2020. Three equation models are developed to examine the impacts of tax structures on economic growth, which are gross domestic product per capita (GDPPC), foreign direct investment (FDI), and unemployment (UE). The study employed fixed effects (FE) and random effects (RE) of Generalized Least Square regression in testing the relationship between taxes structure (direct and indirect) and economic development (GDPPC, FDI, and UE). In addition, the cross-sectional dependence (CD) test is used to identify the presence of spatial dependence for FE and RE estimators. Overall, direct and indirect taxes have a significant negative relationship with economic development based on the GDPPC of developing countries. These results indicated that the tax structure in developing countries does not enhance the countries' economic growth. By contrast, for developed countries, a significant positive relationship exists between direct taxes and economic development. Economics and Development; Economics; Public Finance
Keywords: H2; O1; O2; 330; Developed countries; developing countries; direct taxes; economic development; foreign direct investment; indirect taxes; unemployment rate